MTR Survey of Plate Material Used in Structural Fabrication - Brockenbrough, Roger L. (Engineering Journal, 2003)
A statistical survey was made for a broad sample of mill test reports (MTR) of plate grades typically used in building construction including A36, A572, A588, A852, and A514 steels. Tensile properties, impact properties, and chemical compositions were analyzed. The tensile statistics agreed with assumptions made in the development of the AISC Load and Resistance Factor Design Specification for Structural Steel Buildings (LRFD Specification) (AISC, 1999). The yield-tensile ratios varied from 0.61 to 0.94, following the typical trend of increasing yield-tensile ratio with increasing strength level. The mean CVN values at 70ºF were generally over 100 ft-lbs. for all the steels, which is attributable to the fact that the toughness data were generally reported for product with specified minimum values. The minimum CVN values at 70ºF all met or exceeded the 20 ft-lbs. value specified by AISC for plate material over 2 in. thick used for built-up cross sections spliced with complete-joint-penetration groove welds and subjected to tension. The statistical analysis of composition generally indicated good weldability, particularly for A36 and A572 Grade 50.